2022
DOI: 10.1149/1945-7111/ac7084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coordinated Solvent Molecules in Cu-MOF on Enzyme Free Sensing of Glucose and Lactate in Physiological pH

Abstract: Developing a nonenzymatic sweat sensor for selective determination of glucose and lactate holds great significance in clinical diagnostics. Among various catalysts, transition metal-based metal-organic frameworks (MOF) have recently drawn more attention due to their tunable porosity and enhanced electrocatalytic activity. The presence of solvent molecule in the framework can influence both structural and electrochemical properties. In the present work, Copper-terephthalate (CuBDC) MOF was synthesized in a solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A study on the effect of complexation with different solvent molecules on a Cu-terephthalate MOF for nonenzymatic lactate sensing in physiological pH was reported. 110 The study revealed that solvated MOF shows better sensitivity than desolvated MOF for lactate oxidation. The better performance of the solvated MOF was due to the feasible solvent exchange mechanism and ion diffusion inside the MOF.…”
Section: Mofs-based Lactate Sensorsmentioning
confidence: 93%
See 3 more Smart Citations
“…A study on the effect of complexation with different solvent molecules on a Cu-terephthalate MOF for nonenzymatic lactate sensing in physiological pH was reported. 110 The study revealed that solvated MOF shows better sensitivity than desolvated MOF for lactate oxidation. The better performance of the solvated MOF was due to the feasible solvent exchange mechanism and ion diffusion inside the MOF.…”
Section: Mofs-based Lactate Sensorsmentioning
confidence: 93%
“…A few MOF materials have been used for enzyme-free lactate sensing so far. [104][105][106][107][108][109][110] Wang et al reported the fabrication of flexible amine-functionalized graphene paper (NH 2 -GP) modified with the 2D-oriented assembly of Cu 3 BTC 2 MOF. 104 The modular approach facilitates high MOF particle loading and organized monolayer disposition on NH 2 -GP to form the paper electrode.…”
Section: Mofs-based Lactate Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several types of nanomaterials, including metal nanoparticles (NPs), metal oxides, metal–organic frameworks (MOFs), , conducting polymers, , molecularly imprinted polymers, , carbon, and composite materials, are potential candidates for nonenzymatic lactate sensors. Among these materials, metal oxide nanomaterials, especially transition metal oxides, offer several important advantages, such as easy synthesis, high stability, tunable morphology, adjustable porosity, and versatile functionalization.…”
Section: Introductionmentioning
confidence: 99%